At Risk of Social Exclusion. Labor Market Disadvantage of Ex-Convicts – The Case of Poland - Nowak, Beata Maria (Przegląd Badań Edukacyjnych (Educational Studies Review), 2018)
The study on the risk of social exclusion of former convicts, presented in the article, resulting from their belonging to a disadvantaged group in the labour market, was based on the quantitative strategy (diagnostic survey). The study refers to the retrospective description by penitentiary recidivists of their own activities undertaken in the search for permanent employment in non-detention periods, the nature of the job sought, the motives behind it and the manner in which it was sought, and the frequency of employment. The results of the study indicate the activeness of the vast majority of former prisoners in the area of searching for a job. People over 50 are the least active group. The motivations to take up a job depend on the place of residence and the level of education of the convicts. They look for a job most often using the support of employment offices (the most active ones are people aged 31–40). The younger the ex-convicts and the higher the level of their education, the more often their usage of the Internet and the recommendations of acquaintances. Job offers in the construction industry were among the most sought after. The lower the education level of ex-prisoners, the more common their unemployment. People in small towns and villages most often fail in their efforts to get a job. The results of the study may be used to modernise the post-penitentiary assistance system, including the design of re-adaptation and re-integration support for ex-convicts in the field of employment, based on their socio-demographic profiles (matching motives, needs and personal resources with environmental opportunities) and to counteract discriminatory behaviours of employers.